Smart trends in information technology and computer communications : first international conference, SmartCom 2016, Jaipur, India, August 6-7, 2016, revised selected papers /: first international conference, SmartCom 2016, Jaipur, India, August 6-7, 2016, revised selected papers. (2016) - Unknown
No abstract available